Who Carries the Burden of the Value-Added Tax? Evidence from Germany - Samina Sultan (Center for Economic Studies and Ifo Institute (CESifo), 2020)
The value-added tax is one of the most important tax revenue sources in many countries. However, it is sometimes considered unfair as it ultimately hits consumption, and poorer households spend a greater share of their income on consumption. But this depends on whether, and to what degree, the value-added tax is actually passed on to consumers. Exploiting an exogenous value-added tax reform in Germany, I use an event study and a differences-in-differences approach to investigate the pass-through to consumers for a wide range of commodities. On average, I find a modestly positive but statistically insignificant effect on prices. However, there are differences in tax incidence between commodity groups and anticipatory price effects well in advance of the actual implementation of the value-added tax reform.
Keywords: E31; H25; H22; H31; 330; consumer price index; value-added tax; tax incidence; fiscal policy